Relationship Between Increases Anticardiolipin Titer with CMV Infection In Pregnant Women - Abbas, Nahida Raheem; Jameel, Yousor Majid; Mahdi, Ali Abdul Hussian (Diyala Journal of Medicine, 2018)
Background: Recurrent miscarriage is a severe medical problem occurs in women infected with cytomegalovirus and associated with anticardiolipin antibodies IgM. Objective: To estimate the prevalence of anticardiolipin antibodies in pregnant women with cytomegalovirus infection and history of recurrent loss. Patients and Methods: One hundred women (21-41) years old with recurrent pregnancy loss. Samples were taken from Al-yarmook and Baghdad hospital. This study group was subdivided into four subgroups depends on times of abortion. Anticardiolipin (IgM) and cytomegalovirus antibodies were estimated in the sera by the enzyme linked immunosorbent assay method and compared with 50 apparently healthy pregnant volunteers as a control group at the same age range. Results: It was observed that there is a positive correlation coefficient between anticardiolipin and cytomegalovirus titer (r=0.34729). Also there is significantly difference (t-test, P< 0.05) between mean of anticardiolipin and cytomegalovirus titers of study and control groups. Conclusion: Anticardiolipin antibodies IgM may be associated with first trimester recurrent abortions for women infected with cytomegalovirus.